2021
DOI: 10.3389/fmicb.2021.665975
|View full text |Cite
|
Sign up to set email alerts
|

Different Responses of Soil Bacterial Communities to Nitrogen Addition in Moss Crust

Abstract: Bacterial communities in soil serve an important role in controlling terrestrial biogeochemical cycles and ecosystem processes. Increased nitrogen (N) deposition in Northwest China is generating quantifiable changes in many elements of the desert environment, but the impacts of N deposition, as well as seasonal variations, on soil bacterial community composition and structure are poorly understood. We used high-throughput sequencing of bacterial 16S rRNA genes from Gurbantünggüt Desert moss crust soils to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…On the one hand, the effect of biochar addition on plant growth varies with type and dosage of biochar [ 16 ]. On the other hand, the community structure is directly associated with soil chemical properties, such as C or N levels [ 45 ], the addition of biochar increased the plant absorption of phosphorus by influencing the rhizosphere microorganism and increased the supply of available phosphorus in soil [ 4 , 46 ]. Other studies also found the content of soil C, N, and P in the whole growing season were 2.65–44.4, 0.02–0.32, and 0.3–0.80 g/kg after biochar addition [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the effect of biochar addition on plant growth varies with type and dosage of biochar [ 16 ]. On the other hand, the community structure is directly associated with soil chemical properties, such as C or N levels [ 45 ], the addition of biochar increased the plant absorption of phosphorus by influencing the rhizosphere microorganism and increased the supply of available phosphorus in soil [ 4 , 46 ]. Other studies also found the content of soil C, N, and P in the whole growing season were 2.65–44.4, 0.02–0.32, and 0.3–0.80 g/kg after biochar addition [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Snow-cover (6–16 cm) is during winter ( Hui et al., 2022 ), mainly from November to March (Stable snow period: 100-150 days) ( Zhang et al., 2022b ). The vegetation in China’s largest fixed and semi-fixed desert is dominated by Haloxylon ammolondren , Haloxylon persicum , Ephedra distachya and Ceratoides latens , with well-developed BSCs widely dispersed, moss crusts distributed under the plant canopy and in plant gaps, some algal crusts distributed on the bare ground, and only a few lichens distributed ( Huang et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The distance between each sample area was greater than 20 m. Besides, the split-plot experiment involved two snow treatments in main plots: (1) snow-cover (natural snow cover) (S), and (2) Snow-uncover (covered with tarpaulin before snowfall and removed after snowfall) (UnS). According to the 3.6 g N·m −2 ·year −1 atmospheric N deposition during the past decade ( Huang et al., 2015 ), each application with a three-level N addition of 15 NH 4 15 NO 3 solution (dissolved in 100 ml non-ionized water) in sub-plots, which was added and sprayed evenly on the sample square with a sprinkler on November 1, 2018 ( Huang et al., 2021 ): (1) high N (7.2 g N·m −2 ·year −1 ) (H), (2) moderate N (3.6 g N·m −2 ·year −1 ) (M), (3) light N (1.8 g N·m −2 ·year −1 ) (L), and each application had three replicate plots. A portion of the collected soil samples was quickly packed on dry ice, brought back to the laboratory, and kept in a freezer (−80°C) within 12 h. The other portion of each uniform sample was divided into several parts and air–dried for analysis of soil nutrients and enzymes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil microorganisms play an essential role in the soil ecological and biogeochemical processes, including carbon and nitrogen cycling for plant nutrient uptake [18]. The complexity of the microbial network increases significantly with straw return [19].…”
Section: Introductionmentioning
confidence: 99%